Transcutaneous PCO2 Monitoring in Newborn Infants During General Anesthesia Is Technically Feasible. (October 2016) - Karlsson, Victoria; Sporre, Bengt; Ågren, Johan
Abstract : BACKGROUND: Transcutaneous (TC) measurement of PCO2 (TC PCO2 ) is a well-established method to monitor assisted ventilation in neonatal intensive care, but its use in the operating room is limited, and the data regarding its performance during general anesthesia of the newborn are lacking. The aim of this study is to evaluate the performance of continuous TC PCO2 monitoring during general anesthesia in newborn infants. METHODS: Infants ( n = 25) with a gestational age of 23 to 41 weeks and a birth weight of 548 to 4114 g were prospectively enrolled. During general anesthesia and surgery, TC PCO2 was measured continuously and recorded at 1-minute intervals. Five-minute mean values were compared with simultaneously obtained blood gas (BG) analyses of PCO2 . Only the first paired TC and BG samples were used in this analysis. We defined precision as 2.1 times the standard deviation of the difference of the 2 samples. P < .01 was considered statistically significant. RESULTS: We obtained samples from 25 infants. The difference between TC and BG was 0.3 ± 0.7 kPa (mean ± standard deviation) giving a precision of 1.47 kPa. Nineteen of twenty-five (76%) sample pairs displayed a difference of <1 kPa (99% confidence interval, 48%–92%, P = .016). The difference in paired samples was similar for different gestational and postnatal ages and did not appear to be affected by electrocautery. CONCLUSIONS: In this small study, we did not demonstrate that TC CO2 monitoring was accurate at P < .01. This partly reflects the small size of the study, resulting in wide 99% confidence bounds. Abstract : Published ahead of print July 26, 2016.